Analysis and Evaluation of Tracker Tag Efficiency. (12th January 2023) - Hernández-Orallo, Enrique; Armero-Martínez, Antonio; Calafate, Carlos T.; Manzoni, Pietro
Abstract : Tracker tags, such as Apple's AirTags and Tile's trackers, are small and cheap devices for finding lost items. Tags use Bluetooth technology and community tracking to find the location of lost tags whenever a compatible smartphone passes nearby. When we lose a tag, several questions may arise, like what are the chances of finding it? Or, when will we receive a notification of its detection? Unfortunately, companies such as Apple or Tile do not provide technical information about the efficiency of their tags. Thus, this paper is aimed at answering those questions based on a methodological analysis and evaluation of tags' efficiency. The main aspects that impact the efficiency of finding a lost tag are the detection range, community size, and human mobility. These aspects are evaluated in a campus scenario, showing that the probability of finding lost tags is very high: more than 98% of them were found, and the average detection time was about 1 hour.